(untitled) (Intent Research Scientific Journal, 2023)
The purpose of this article is to consider the advantages and disadvantages of using veneers in modern aesthetic dentistry. Veneers are ultra-thin shells made of ceramics (porcelain) or composite polymers, glued to the front surface of the tooth, and in many cases are an excellent alternative to crowns. They provide a more conservative approach to changing the color, size and shape of the tooth. They can also hide unwanted defects, for example, teeth stained with tetracycline, traumatic injuries or the results of root canal treatment.